2022
DOI: 10.1186/s12877-022-03107-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving individualized prescription in patients with multimorbidity through medication review

Abstract: Background Older patients tend to have multimorbidity, represented by multiple chronic diseases or geriatric conditions, which leads to a growing number of prescribed medications. As a result, pharmacological prescription has become a major concern because of the increased difficulties to ensure appropriate prescription in older adults. The study’s main objectives were to characterize a cohort of older adults with multimorbidity, carry out a medication review and compare the pharmacological dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…The degree of frailty was not a differential element in the intensity of the model’s effect. Nevertheless, notably, a recently published before–after study reported that the application of a PCP model was valid for reducing polypharmacy, MRCI, and DBI in patients with a moderate or advanced degree of frailty and multimorbidity but who were not necessarily at EOL [ 32 ]. However, in this last case, the results could be because people with a more advanced frailty index were entering a final stage of life, whereas the PCP model has greater efficacy when optimizing pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of frailty was not a differential element in the intensity of the model’s effect. Nevertheless, notably, a recently published before–after study reported that the application of a PCP model was valid for reducing polypharmacy, MRCI, and DBI in patients with a moderate or advanced degree of frailty and multimorbidity but who were not necessarily at EOL [ 32 ]. However, in this last case, the results could be because people with a more advanced frailty index were entering a final stage of life, whereas the PCP model has greater efficacy when optimizing pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The most common medication change related to priority assessment in SPPiRE was a dose change (compared with stopping a medicine for the PIP assessment and brown bag processes), indicating that optimizing medications in polypharmacy is not just about changes in the number of medicines. A recently completed uncontrolled before‐after study of a similar patient‐centred medication review resulted in reduced medication regime complexity and enhanced adherence 38,39 . Future research in this area should focus on the development and evaluation of tools to assist both GPs and older people with multimorbidity in the identification of treatment priorities.…”
Section: Discussionmentioning
confidence: 99%
“…A recently completed uncontrolled before‐after study of a similar patient‐centred medication review resulted in reduced medication regime complexity and enhanced adherence. 38 , 39 Future research in this area should focus on the development and evaluation of tools to assist both GPs and older people with multimorbidity in the identification of treatment priorities.…”
Section: Discussionmentioning
confidence: 99%
“…The application of PCP models is clearly established ( 37 41 ) in the scientific literature and can identify inappropriate prescriptions, optimize polypharmacy and improve medication adherence in different profiles of older patients. Additionally, the use of tools with explicit criteria [OncPal ( 42 ) and STOPPFrail ( 28 )] to determine inappropriate drugs at the EOL is valid for deprescription and produces beneficial effects ( 43 ).…”
Section: Discussionmentioning
confidence: 99%